Swift justice ; The Homeopathic alternative ; In "style" [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Summary: Looks at the investigation of the connection of Manila Mayors program to end drug problem with the murder of drug addicts and pushers; the medical science of homeopathy; and Elsa Klensch taking a look at Philippine fashion and design.